2017
DOI: 10.1016/j.ijhcs.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Community Reminder: Participatory contextual reminder environments for local communities

Abstract: Many projects have looked at how communities can co-design shared online repositories, such as Wikimapia and Wikipedia. However, little work has examined how local communities can give advice and support to their members by creating context-aware reminders that may include advice, tips and small requests. We developed the Community Reminder environment, a smartphone-based platform that supports community members to design and use context-aware reminders. We have conducted a one-month field study of Community R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…These studies have shown that community engagement is possible and that a suitable reward system can encourage sufficient community participation. Recent research conducted by Sasao et al (2017) has shown that reminders can broaden participation in local communities. This particular research also provided evidence that involving the community offers many benefits that contribute to the success of a specific project as a whole.…”
Section: Engagement Of Smart Community and Smart Citymentioning
confidence: 99%
“…These studies have shown that community engagement is possible and that a suitable reward system can encourage sufficient community participation. Recent research conducted by Sasao et al (2017) has shown that reminders can broaden participation in local communities. This particular research also provided evidence that involving the community offers many benefits that contribute to the success of a specific project as a whole.…”
Section: Engagement Of Smart Community and Smart Citymentioning
confidence: 99%
“…Spatial information such as location information is considered an essential part in context-aware messaging services. The guidance and notification services, such as Community Reminder [9], depend on location in order to execute tasks. Location is commonly used in the area of social network services to facilitate greater interaction between agents such as groups of nearby friends in the services.…”
Section: A Understanding the Spatial Environment For Context-aware Mmentioning
confidence: 99%
“…The service ontology enhances and supports knowing sharing capabilities as well as messaging functionalities for guidance and notification purposes such as work done in Community Reminder. Community Reminder [9] provides the user with reminders and situations that can be applied in many ways. Mona-ServOnt contains similar context information that can be applied to offer guidance and notification services.…”
Section: A the Guidance And Notification Service Ontologymentioning
confidence: 99%
“…Some learning analytics projects have explored proactive capabilities of data-driven environments based on prediction (Okubo et al, 2017b) and mobile alerts (Straumsheim, 2013), although they do not fully respond to the dynamic contexts of learners. Context-responsive notifications have been used to provide personalized feedback regarding energy consumption (Igarashi et al, 2016) and safety (Sasao et al, 2017). However, they do not explicitly support learning processes.…”
Section: 5mentioning
confidence: 99%
“…This can help go beyond the limits of adaptive learning systems that rely on data about what happened in the past. As multimodal notifications can be developed in co-design workshops involving different stakeholders (Sasao et al, 2017), we opt for an approach that encourages teachers and students to design notifications in face-to-face settings or by using asynchronous collaboration tools.…”
Section: 51mentioning
confidence: 99%